Where do banks end and NBFIs begin? - Viral V. Acharya; Nicola Cetorelli; Bruce Tuckman (Federal Reserve Bank of New York, 2024)
In recent years, assets of nonbank financial intermediaries (NBFIs) have grown significantly relative to those of banks. These two sectors are commonly viewed either as operating in parallel, performing different activities, or as substitutes, performing substantially similar activities, with banks inside and NBFIs outside the perimeter of banking regulation. We argue instead that NBFI and bank businesses and risks are so interwoven that they are better described as having transformed over time, rather than as having migrated from banks to NBFIs. These transformations are at least in part a response to regulation and are such that banks remain special as both routine and emergency liquidity providers to NBFIs. We support this perspective as follows: (i) the new and enhanced financial accounts data for the United States ("From Whom to Whom") show that banks and NBFIs finance each other, with NBFIs especially dependent on banks; (ii) case studies and regulatory data show that banks remain exposed to credit and funding risks, which at first glance seem to have moved to NBFIs, and also to contingent liquidity risk from the provision of credit lines to NBFIs; and (iii) empirical work confirms bank-NBFI linkages through the correlation of their abnormal equity returns and market-based measures of systemic risk. We discuss some potential regulatory responses, including treating the two sectors holistically, recognizing the implications for risk propagation and amplification, and exploring new ways to internalize the costs of systemic risk.
Keywords: G01; G21; G23; G2; 330; nonbank financial intermediaries; nonbanks; shadow banking; bank regulation; regulatory arbitrage; systemic risk; credit lines; derivatives margin